Review of valuation methods of preference-based measures of health for economic evaluation in child and adolescent populations: where are we now and where are we going? - Rowen, D; Rivero-Arias, O; Devlin, N; Ratcliffe, J (Springer, 2020)
Methods for measuring and valuing health benefits for economic evaluation and health technology assessment in adult populations are well developed. In contrast, methods for assessing interventions for child and adolescent populations lack detailed guidelines, particularly regarding the valuation of health and quality of life in these age groups. This paper critically examines the methodological considerations involved in the valuation of child- and adolescent-specific health-related quality of life by existing preference-based measures. It also describes the methodological choices made in the valuation of existing generic preference-based measures developed with and/or applied in child and adolescent populations: AHUM, AQoL-6D, CHU9D, EQ-5D-Y, HUI2, HUI3, QWB, 16D and 17D. The approaches used to value existing child- and adolescent-specific generic preference-based measures vary considerably. While the choice of whose preferences and which perspective to use is a matter of normative debate and ultimately for decision by reimbursement agencies and policy makers, greater research around these issues would be informative and would enrich these discussions. Research can also inform the other methodological choices required in the valuation of child and adolescent health states. Gaps in research evidence are identified around the impact of the child described in health state valuation exercises undertaken by adults, including the possibility of informed preferences; the appropriateness and acceptability of valuation tasks for adolescents, in particular tasks involving the state ‘dead’; anchoring of adolescent preferences; and the generation and use of combined adult and adolescent preferences.